Chest radiography predictor of COVID-19 adverse outcomes. A lesson learnt from the first wave. Issue 7 (July 2021) - Flor, N.; Casazza, G.; Saggiante, L.; Savoldi, A.P.; Vitale, R.; Villa, P.; Martucci, F.; Ballone, E.; Castelli, A.; Brambilla, A.M.
Abstract : AIM: To assess the role of a severity score based on chest radiography (CXR) in predicting the risk of adverse outcomes in coronavirus disease 2019 (COVID-19). MATERIALS AND METHODS: Of the patients who presented to L. Sacco Hospital (Milan, Italy) between 21 February and 31 March 2020, patients with a laboratory confirmation of COVID-19 who also underwent a CXR were included in the study. To quantify the extent of lung involvement, each CXR image was given a score (Milan score), ranging from 0 to 24, depending on the presence of reticular pattern and/or ground-glass opacities and/or extensive consolidations in each of the 12 areas in which the lungs were divided. The score was calculated by an expert radiologist, blinded to laboratory tests. The ability of the Milan score to predict hospital admission and mortality, after adjusting for some variables (age; gender; comorbidities; time between symptoms onset and admission), using univariate and multivariate statistical analysis was investigated retrospectively. RESULTS: Among the 554 patients, 115 of which (21%) had a negative CXR, the in-hospital mortality was 16% (90/554). At univariate analysis, age, gender, and comorbidities were significant predictors of mortality and hospital admission. At multivariate analysis, adjusting for age and gender, the Milan score was an independent predictor of mortality and hospitalisation. In particular, patients with a Milan score ≥ 9 had a mortality risk five-times higher than those with a lower score. Other independent predictors of mortality were gender and age. CONCLUSIONS: The CXR Milan score was an independent predictive factor of both in-hospital mortality and hospital admission. Highlights: Evidence on chest x-ray predictive value for COVID-19 adverse outcomes is limited. The CXR [Blinded] score was found to be independent predictive factor of mortality. Chest radiography has a pivotal role in the management of COVID-19 patients.